Successful Treatment of Narcolepsy and Cataplexy: A Review. Issue 4 (3rd June 2005) - Lockrane, B; Bhatia, P; Gore, Robin
Abstract : A 25-year-old woman with narcolepsy and cataplexy was treated with well-recognized drugs for these conditions. Because she did not respond, a decision was made to treat her with sodium oxybate.